Writing the Northern Powerhouse: evaluating the Northern Writers' Awards as a potential model of intervention for addressing regional representation in the 'London-Centric' UK literary industry. Issue 1 (2nd January 2019) - Shaw, Katy
Abstract: Despite the UK government's Northern Powerhouse agenda, the UK literary industry remains staunchly focused on a predominantly London-base. When it comes to Northern writers, representations of the North in contemporary literature and Northern voices on the stage, small and big screens, UK government has suggested that the literary industry is guilty of persistently underrepresenting the 55.4 million members of the public who live outside the capital city. This research adopts a case study approach to the problem, examining one regional creative industry award, the Northern Writers' Awards (NWAs), as a potential model of intervention for enhancing participation, professional development and talent pipelines of Northern writers to the wider UK literary industry. The research analyses how and why the NWAs: enable career development opportunities for creative talent through partnership-based training and knowledge exchange; retain the economic impact of regional creative talent to improve the economy of the North by developing creative writers within the region; and enhance diversity in the UKwriting industry by addressing issues of representation and by reaching writers from all backgrounds across the North.